Self-Protection Technology for Application-Aware Network Management System - Fei Wang (Dianxin kexue)
With the development of mobile operational business，there is ever-growing requirement for centralization of NMSS（network management and support system）and network supervision. At present，increasing devoid of fast and effective monitoring means has taken place，especially on construction of application aware-oriented security system for network management，which could find and deal with problems of NMSS platform before repercussions from user application-aware，thus to improve capabilities of self-protection management and support. Therefore，combined with the rapid development of mobile 4G，the customer experience and system operation for the network from the perspective of the monitoring platform was built，the emergency response capacity of the IT system was enhanced，and the service level of network was promoted abidingly.